2021
DOI: 10.1177/23779608211059265
|View full text |Cite
|
Sign up to set email alerts
|

Case Study Analysis as an Effective Teaching Strategy: Perceptions of Undergraduate Nursing Students From a Middle Eastern Country

Abstract: Background: Case study analysis is an active, problem-based, student-centered, teacher-facilitated teaching strategy preferred in undergraduate programs as they help the students in developing critical thinking skills. Objective: It determined the effectiveness of case study analysis as an effective teacher-facilitated strategy in an undergraduate nursing program. Methodology: A descriptive qualitative research design using focus group discussion method guided the study. The sample included undergraduate nursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
(39 reference statements)
0
19
0
2
Order By: Relevance
“…However, recently there has been a shift towards adopting problem‐based and case‐based learning methods in the curricula, which encourage more active participation 17 . This adjustment is essential as data has illustrated that case studies that are problem‐based, student‐centred and lecturer‐facilitated assist students to develop critical thinking skills 18 . A study on undergraduate nursing students in a middle Eastern country found that students exposed to such teaching approaches are better prepared to integrate theory with practice, as they have been given the opportunity to solve case scenarios 18 .…”
Section: Resultsmentioning
confidence: 99%
“…However, recently there has been a shift towards adopting problem‐based and case‐based learning methods in the curricula, which encourage more active participation 17 . This adjustment is essential as data has illustrated that case studies that are problem‐based, student‐centred and lecturer‐facilitated assist students to develop critical thinking skills 18 . A study on undergraduate nursing students in a middle Eastern country found that students exposed to such teaching approaches are better prepared to integrate theory with practice, as they have been given the opportunity to solve case scenarios 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, a series of advantages were listed regarding the game's characteristics, including dynamic, playful, game layout, usability, attractiveness, user-friendly, interactive, structure by categories, and clinical cases. Regarding the latter, case study analysis is an active, problem-based, studentcentered learning and helps develop critical thinking skills (25). The implemented case study as a teaching strategy in the family nursing game significantly positively affected the perception of teaching effectiveness (26).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, [4] identify that collaborative learning improved students' cognitive performance [4]. Lastly, Seshan et al [5] reported that case studies are "effective for imparting professional knowledge and skills in undergraduate nursing education and it results in a deeper level of learning and helps in the application of theoretical knowledge into clinical practice. It also broadened students' perspectives and improved their cooperation capacity and their communication with each other.…”
Section: Introductionmentioning
confidence: 99%
“…It also broadened students' perspectives and improved their cooperation capacity and their communication with each other. Finally, it enhanced student's judgment and critical thinking skills which are key for their success" [5] (para. 1) With this evidence, a case study approach with weekly study sessions was implemented for this remediation plan.…”
Section: Introductionmentioning
confidence: 99%